ANALISIS BENTUK KONTAK BAHASA DALAM TUTURAN SISWA DI MTs AL-MUTTAQIN SUNGAI UNGAR: KAJIAN SOSIOLINGUISTIK - Filza Aiza; Fabio Testy Triance Loren (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language contact is a common sociolinguistic phenomenon in bilingual communities, including students who use regional and Indonesian languages interchangeably in daily communication. This study aims to describe the forms of language contact found in the utterances of students at MTs Al-Muttaqin Sungai Ungar. The research employed a qualitative descriptive approach. Data were collected through observation, audio recording, note-taking, interviews, questionnaires, and documentation. The research subjects consisted of students of MTs Al-Muttaqin Sungai Ungar selected using purposive sampling. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that students experience bilingualism, with Malay functioning as the first language and Indonesian as the second language used in formal communication. This bilingual condition gives rise to language contact phenomena in the form of code switching and code mixing during classroom and non-classroom interactions. Code switching occurs when students change language according to the interlocutor or communication context, whereas code mixing appears through the insertion of Malay lexical elements into Indonesian utterances. These findings indicate that language contact among students is influenced by bilingual competence and the sociolinguistic environment in which they interact. The study contributes to the understanding of language contact phenomena among junior high school students in bilingual communities.